2004
DOI: 10.1002/sat.796
|View full text |Cite
|
Sign up to set email alerts
|

Layered coding for satellite‐plus‐terrestrial multipath correlated fading channels

Abstract: SUMMARYThis paper introduces two alternative layered-coding (LC) structures suitable for a combination of a geostationary (GEO) satellite and a terrestrial system providing multicasting multimedia services. Both schemes include a RAKE receiver and their performance results are presented under realistic satellite and terrestrial channel conditions. The structures are based on mapping the coded bits either onto 8-PSK symbols or onto QPSK symbols. The LC parameters (such as the interleaver design and the convolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The penalty associated with the latter choice is increased decoding complexity and delay. As an example of the layered coding applied to hybrid/integrated satellite system to provide MBMS, the previous research in [9] proposed a layered coding scheme with serially concatenated turbo codes, and demonstrated performance improvement. In this scheme, a receiver in the deep fading condition selects a decoding scheme for the fully concatenated codes, so that it can produce a large coding gain, while a receiver in the mild channel condition selects a decoding scheme for a simple outer code only and, thus, reduces the decoder complexity.…”
Section: Layered Coding For Satellite Systemmentioning
confidence: 99%
“…The penalty associated with the latter choice is increased decoding complexity and delay. As an example of the layered coding applied to hybrid/integrated satellite system to provide MBMS, the previous research in [9] proposed a layered coding scheme with serially concatenated turbo codes, and demonstrated performance improvement. In this scheme, a receiver in the deep fading condition selects a decoding scheme for the fully concatenated codes, so that it can produce a large coding gain, while a receiver in the mild channel condition selects a decoding scheme for a simple outer code only and, thus, reduces the decoder complexity.…”
Section: Layered Coding For Satellite Systemmentioning
confidence: 99%
“…Comparing the layered coding structures, it has been shown that Structure B leads to better coverage efficiency due to its improved BER performance [8]. Structure A has worse performance than Structure B, but, due to its higher spectral efficiency, it can accommodate twice the throughput of Structure B.…”
Section: Codingmentioning
confidence: 99%